Genetically Regulated Temporal Variation of Novel Courtship Elements in the Hawaiian Cricket Genus Laupala - Fergus, Daniel J. (2010)
The Hawaiian cricket genus Laupala (Gryllidae: Trigonidiinae) has undergone rapid and extensive speciation, with divergence in male song and female acoustic preference playing a role in maintaining species boundaries. Recent study of interspecific differences in the diel rhythmicity of singing and mating, suggests that temporal variation in behavior may reduce gene flow between species. In addition, Laupala perform an elaborate and protracted courtship, providing potential for further temporal variation. However, whether these behavioral differences have a genetic basis or result from environmental variation is unknown. We observed courtship and mating in a common garden study of the sympatric species, Laupala cerasina and Laupala paranigra. We document interspecific differences in the onset and duration of courtship, spermatophore production rate, and diel mating rhythmicity. Our study demonstrates a genetic contribution to interspecific behavioral differences, and suggests an evolutionary pathway to the origins of novel timing phenotypes.